2003
DOI: 10.5194/acp-3-377-2003
|View full text |Cite
|
Sign up to set email alerts
|

Twilight tropospheric and stratospheric photodissociation rates derived from balloon borne radiation measurements

Abstract: Abstract.A new ligthweight multichannel moderate bandwidth filter instrument designed to be flown on balloons, is described. The instrument measures the radiation field within the short UV (center wavelength at 312 nm) and long UV (center wavelength at 340 nm). The angular and spectral characteristics of the instrument are discussed and the calibration procedure outlined. Measurements made during a stratospheric balloon flight at twilight conditions from GapTallard, France, are presented and compared with stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In comparison, the stratosphere UV model developed for this study generated similar levels for UVC and UVB at 20–50 km ASL: 0.00550–5.20 and 4.16–17.1 W/m 2 , respectively. Our model was consistent within the range of measured values by Kylling et al (2003), who flew a UV radiometer to 30.5 km ASL in the stratosphere over France (∼44.5°N), recording measurements at 312 and 340 nm across a solar zenith range of 76–94° in flight.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In comparison, the stratosphere UV model developed for this study generated similar levels for UVC and UVB at 20–50 km ASL: 0.00550–5.20 and 4.16–17.1 W/m 2 , respectively. Our model was consistent within the range of measured values by Kylling et al (2003), who flew a UV radiometer to 30.5 km ASL in the stratosphere over France (∼44.5°N), recording measurements at 312 and 340 nm across a solar zenith range of 76–94° in flight.…”
Section: Discussionsupporting
confidence: 91%
“…The next-generation E-MIST payload system will also aim to incorporate a dosimeter for measuring ionizing radiation levels in the stratosphere. Until a reflight opportunity for the E-MIST payload, independent radiation measurements from the stratosphere can be used for evaluating the fidelity of the UV model developed herein ( e.g., Kylling et al, 2003; Mertens et al, 2016). Our forecast suggested that stratosphere UVB/UVC levels (averaged between 20 and 50 km ASL) would be similar to martian conditions calculated by Schuerger et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new NILUCUBE has had improved input optics which deviates less than 5% from the ideal cosine response for zenith angles smaller than 85 • . By combining the measurements from all heads, the actinic flux may be derived as shown by Kylling et al (2003).…”
Section: A22 Nilucube Uv Radiometermentioning
confidence: 99%
“…A new version of the NILUCUBE instrument of the Norwegian Institute for Air Research (NILU) described by Kylling et al (2003) was developed for HIBISCUS. The new sensor has six channels in each of its six heads.…”
Section: A22 Nilucube Uv Radiometermentioning
confidence: 99%